1988
DOI: 10.2466/pr0.1988.63.1.163
|View full text |Cite
|
Sign up to set email alerts
|

Intelligence and Emotional/Behavioral Factors as Correlates of Achievement in Child Psychiatric Inpatients

Abstract: This study investigated the extent to which IQ and emotional/behavioral factors were related to tested academic achievement in 56 child psychiatric inpatients. The first part of the study replicated and extended previous research; WISC—R IQs were highly correlated with tested achievement, Verbal IQs being more highly correlated with achievement than were Performance or Full Scale IQs. In the second part of the study which examined the relationship between the emotional/behavioral indices and achievement, only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Reviews of LOC × academic achievement studies have shown internality to be associated with higher average grades and achievement test scores ( Findley and Cooper, 1983 ; Kalechstein and Nowicki, 1997 ). In some instances, the LOC achievement association remained significant even when IQ scores were controlled for ( Ollendick and Ollendick, 1976 ; Brown, 1980 ; Finch et al, 1988 ). Past research suggests that LOC orientation precedes academic achievement rather than vice versa ( Stipek, 1980 ).…”
Section: Introductionmentioning
confidence: 93%
“…Reviews of LOC × academic achievement studies have shown internality to be associated with higher average grades and achievement test scores ( Findley and Cooper, 1983 ; Kalechstein and Nowicki, 1997 ). In some instances, the LOC achievement association remained significant even when IQ scores were controlled for ( Ollendick and Ollendick, 1976 ; Brown, 1980 ; Finch et al, 1988 ). Past research suggests that LOC orientation precedes academic achievement rather than vice versa ( Stipek, 1980 ).…”
Section: Introductionmentioning
confidence: 93%
“…The STAIC has been used by psychologists, educators, sports scientists, and others in a variety of ways, such as adaptation or standardization procedures (e.g., Bauermeistez, Colon-Fumero, Villamil-Forastieri, & Spielberger, 1986; Brook & Knapp, 1976; Cross & Huberty, 1993; Day, Knight, El-Nakadi, & Spielberger, 1986; Finch, Kendall, & Montgomery, 1976; Gaudry & Poole, 1975; Hedl & Papay, 1982; Soga, 1983). The STAIC has also been used as a criterion to test the validity and reliability of other instruments (e.g., Nunn, 1988; Nunn, Parish, & Worthing, 1983; Reynolds, 1980; Silverman, Fleisig, Rabian, & Peterson, 1991) and employed as a psychodiagnostic tool for measuring anxiety variables (e.g., Alpert-Gillis, 1990; Finch, Blount, Saylor, & Wolfe, 1988; Fisher, Allen, & Kose, 1996; Hodges, 1990; Houston, Fox, & Forbes, 1984; Kane & Kendall, 1989). The purpose of this study was to validate the State-Trait Anxiety Inventory for Children (STAIC) in the Greek population.…”
mentioning
confidence: 99%